Health Promoting Lifestyle among Domestic and International Students in Russia: A Comparative Analysis - Evgeni NIKOLAEV; Elena LAZAREVA; Nadezhda LANTSOVA; Lyubov ROMANOVA; Rahmatulla YAKUBOV (Communications of International Proceedings, 2020)
Students belong to population groups that have a high risk of health problems and risky behaviors. The use of the Health-promoting lifestyle profile allows the identification of factors influencing health keeping behavior. The study involved 205 students from various Russian universities, 97 of them were domestic students, 108 – international students. Participants filled out the Health Promoting Lifestyle Profile. According to the results, both groups of students had sufficient resources to maintain psychosocial well-being. The adherence to a healthy lifestyle in the groups of domestic and international students had its own gender and age specifics. The reason for these differences may be not only cultural factors associated with religious, educational, health-improving traditions. The differences may also be based on economic factors.
Keywords: Health Promoting Lifestyle; Domestic Students; International Students; Russia.